Assessment of balimbing (Averrhoa carambola) fruit for jam making - Magpusao, Mary Louise Tacderas (University of the Philippines School of Science and Technology, 2013)
This study covered the characterization of balimbing fruit at two maturity levels, namely unripe and ripe and the acceptability of balimbing jam.